Extraction, extrusion processing, and functional behavior of plant proteins - Xiao, Ruoshi (Kansas State University, 2024)
Due to environmental, health, social, and ethical concerns associated with animal-based protein production, there is a growing demand for alternative protein sources. Plant-based proteins offer advantages such as cost-effectiveness, environmental sustainability, and nutritional value. In addition to widely utilized proteins such as soy protein, pea protein, or wheat gluten, sorghum proteins are gaining interest due to their gluten-free nature and unique functional features. The goal of this study is to extract proteins from grain sorghums and investigate their physicochemical properties and functionalities, as well as exploring physicochemical and functional changes of plant proteins during extrusion texturization. The specific objectives were to: 1) investigate the impact of genotype and fermentation on the physicochemical and functional properties of sorghum kafirins; 2) develop an efficient method for sorghum protein concentrate extraction, optimize its extraction process and analyze their physicochemical and functional properties; 3) evaluate the effects of raw material formulation and extrusion processes on the properties and structural conformation of plant-based proteins (including soy protein, pea protein, and wheat gluten). The extracted kafirins had protein content ranging from 75 to 85%. Protein molecular weights were consistent across different sorghum types but altered after fermentation, likely due to high-temperature fermentation conditions. Kafirin properties, including structure, color, and surface hydrophobicity, varied among sorghum types, with fermentation showing minimal effects. Kafirins from distiller’s grains (DGs) demonstrated lower solubility but varied emulsifying properties, water holding capacity (WHC), and oil holding capacity (OHC). Black sorghum DG kafirin had slightly lower in vitro protein digestibility (around 74%) compared to other sorghum DGs (75-79%), possibly due to higher residue tannin content. A novel process was developed for extracting sorghum protein concentrate with 85% protein content and approximately 95% protein recovery rate. Sorghum proteins extracted from flour exhibited higher α-helix and random coil structures, total sulfhydryl content, WHC, OHC, and in vitro digestibility compared to proteins from sorghum gluten meals, likely due to the different procedures. The sorghum protein concentrate also displayed higher crude fat content, α-helix and random coil structures, surface hydrophobicity, and OHC compared to commercial plant proteins (soy protein, pea protein, and wheat gluten), attributed to differences in amino acid compositions and protein structures. Texturized proteins with varying cold-swelling protein (CS) proportions experienced decreased α-helix and increased β-sheet content post-extrusion, indicating significant conformational changes. Disulfide bonds were identified as primary forces forming fibrous structure integrity. After extrusion, free amino and sulfhydryl groups, along with surface hydrophobicity, experienced a notable decline. Protein digestibility, WHC, and OHC displayed fluctuating patterns with varying CS ratios, whereas emulsifying, foaming, and gel-formation properties deteriorated in texturized proteins. In conclusion, different pretreatments and extraction methods influence sorghum protein properties and functionalities. Extrusion processes significantly alter protein structures and properties. Therefore, the processing method plays an important role in addition to the type of protein source in determining protein functionalities and practical applicability across various plant sources.
Keywords: Plant-based protein; Sorghum protein; Protein extraction; Protein functionality; Extrusion process; Texturized protein